Gross domestic product predictions based on population, rainfall, water inflow and water outflow: A Northern Thailand model - E. Duangdai (2019)
© 2019 Author(s). This work proposes a mathematical model on the relationships between Thailand's agricultural and manufacturing sector Gross Domestic Products (GDPs) and other regional dynamical aspects such as rainfalls and water inflows and outflows from major local dams, and the nation's annual total population. Variables and cross term variables are selected based on their correlations with each other; only those with high correlations are included in the model. Data used to construct and validate the model are from the years 2005-2014. According to the leave-one-out cross validation method, the resulting model gives an average error rate of 0.4547. The model predicts Year 2020 agricultural and manufacturing sector GDPs of 15.72 billion and 0.091 trillion dollars, respectively.